Integration of Modified Luo Converter and ANFIS MPPT in Grid-Tied Photovoltaic Systems - D, Thivya Prasad; R, Anandhakumar; P, Balamurugan (International Research Journal of Multidisciplinary Technovation, 2025)
The sustainable growth of energy solutions depends on the incorporation of renewable energy sources into grid connected systems. This study describes a grid tied photovoltaic (PV) system that uses a modified Luo converter and Maximum Power Point Tracking (MPPT) based on an Adaptive Neuro Fuzzy Inference System (ANFIS). The proposed system integrates a Modified Luo Converter for efficient DC-DC conversion, ensuring stable voltage regulation under varying solar irradiance and temperature conditions. It utilizes an ANFIS based MPPT controller to optimize energy extraction by accurately tracking the PV array’s maximum power point, while an LC filter ensures high quality power delivered to the grid in compliance with grid standards. The developed research, executed utilizing MATLAB 2021a Simulink tool, demonstrates exceptional performance with an efficiency of 94.1% and enhanced grid stability.